2021
DOI: 10.2166/wst.2021.369
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac degradation based on shape-controlled cuprous oxide nanoparticles prepared by using ionic liquid

Abstract: Persulfate oxidation technology is widely used in wastewater treatment, but there are still many disadvantages, such as high energy consumption, side reaction and narrow pH applicability. Copper oxides can activate persulfate steadily with higher efficiency. In this paper, a novel preparation method of shape-controlled cuprous oxide (Cu2O) nanoparticles featured with high catalytic performance was explored. It was found that adding ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) during preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In Figure 1B , the surface of the Cu 2 O NPs was rough and its SAED (inset of Figure 1B ) indicated that the Cu 2 O NPs have a polycrystalline structure ( Chinnaiah et al, 2022 ). The elemental mapping of Cu 2 O NPs ( Figure 1C ) and the corresponding high-resolution transmission electron microscopy (HRTEM) image shown in Supplementary Figure S3 (ESI†) confirmed its high-quality polycrystalline nature ( Huang and Luo, 2021 ). The phase structure and the purity of Cu 2 O NPs were analyzed using X-ray diffraction (XRD).…”
Section: Introductionmentioning
confidence: 76%
“…In Figure 1B , the surface of the Cu 2 O NPs was rough and its SAED (inset of Figure 1B ) indicated that the Cu 2 O NPs have a polycrystalline structure ( Chinnaiah et al, 2022 ). The elemental mapping of Cu 2 O NPs ( Figure 1C ) and the corresponding high-resolution transmission electron microscopy (HRTEM) image shown in Supplementary Figure S3 (ESI†) confirmed its high-quality polycrystalline nature ( Huang and Luo, 2021 ). The phase structure and the purity of Cu 2 O NPs were analyzed using X-ray diffraction (XRD).…”
Section: Introductionmentioning
confidence: 76%
“…2 and 4b). 34,166 IL-Cu 2 ONPs were prepared by adding various concentrations of imidazolium IL with bromide anion. The degradation of IL-Cu 2 ONPs was observed over the entire pH range, which confirmed that the concentrations of reactive oxygen species and the sulfate radical resulting from the cleavage of the interoxide bond to sodium persulfate are responsible for drug decomposition.…”
Section: Agmentioning
confidence: 99%
“…2 A short chronological survey of the timeline for IL-NPs milestones in biotechnological applications. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] experimental evidence for the formation of gold and silver NPs within the structural components of living plants was presented by J. L. Gardea-Torresdey and co-authors in 2002 and 2003. 25,26 Intensive efforts were made to describe the biological applications of ILs-NPs systems with respect to their anticancer activity 18 to subsequently encompass antibacterial therapies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations